Functionalized phenylimidazole-based facial-homoleptic iridium(iii) complexes and their excellent performance in blue phosphorescent organic light-emitting diodes. Issue 16 (18th April 2018) - Kwon, Youngjae; Han, Si Hyun; Yu, Seokhyeon; Lee, Jun Yeob; Lee, Kang Mun
Abstract : Novel phenylimidazole-based blue-emitting iridium complexes were prepared and they showed the excellent electroluminescent performance. Abstract : Herein, we present the preparation of two functionalized phenylimidazole-based facial -homoleptic iridium complexes, FIr ( fac -tris(1-(2, 6-diisopropylphenyl)-2-(4-fluorophenyl)-1 H -imidazolyl)iridium(iii )) andCNIr ( fac -tris(1-(2, 6-diisopropylphenyl)-2-(3-cyanophenyl)-1 H -imidazolyl)iridium(iii )), and their full characterisation by multinuclear NMR spectroscopy and elemental analysis. Investigation of the molecular structures of the two iridium complexes by single-crystal X-ray diffraction revealed the facial -isomerism. Both complexes showed a definite blue-emission band ( λ em = 454 nm forFIr and 462 nm forCNIr ) in solution and film states at ambient temperature. Moreover, the complexes exhibited significantly high phosphorescent quantum efficiencies in a mCP (1, 3-bis( N -carbazolyl)benzene) film doped with 5 wt% system (0.87 forFIr and 0.99 forCNIr ). Thermogravimetric analysis of the complexes displayed their high thermal stabilities as T d5 values (5 wt% loss) above 390 °C. The frontier energy levels of both complexes calculated from the oxidation and reduction potential were measured to be from approximately −6.1 eV (HOMO) to approximately −2.8 eV (LUMO), which indicated their suitability as novel phosphorescent emitters for blue OLEDs. In addition, multi-layer phosphorescent organic light-emitting diodes usingFIr andCNIr as emitters and mCP as a host have been fabricated. The devices exhibited low turn-on voltages and high external quantum efficiencies (18.9% forFIr and 22.5% forCNIr ) with blue phosphorescent emission under CIE y = 0.3 ( y coordinate of Commission Internationale de l'Eclairage). Moreover, the CNIr based device showed stable lifetimes greater than 550 h at 200 cd m −2, which is much longer than that of the common phenylpyridine-type blue triplet emitter based device.